The LTB4-BLT1 axis attenuates influenza-induced lung inflammation by suppressing NLRP3 activation - Cheng Wei; Yitian Xu; Ying Zheng; Lizhe Hong; Chen Lyu; Haibo Li; Bin Cao (Cell Death Discovery)
Abstract The mortality associated with influenza A virus (IAV) infection typically results from excessive immune responses, leading to immunopathological lung damage and compromised pulmonary function. Various immunomodulators are seen beneficial when used in conjunction with direct anti-infection treatment. Leukotriene B4 (LTB4) is a derivative of arachidonic acid (AA) and has been shown to be advantageous for numerous infectious diseases, allergies, and autoimmune disorders. Nonetheless, the function of LTB4 in influenza infection remains unclear. This study demonstrates that LTB4 and its primary receptor BLT1, as opposed to the secondary receptor BLT2, act as a protective immune modulator during influenza infection in bone marrow-derived macrophages and mouse models. Mechanistically, LTB4 promotes K27-linked and K48-linked polyubiquitination of the NLRP3 protein at its K886 and K1023 sites via a cAMP/PKA-dependent pathway, which inhibits NLRP3 inflammasome assembly and thereby diminishes subsequent NLRP3 inflammasome activation. The consequent decline in the release of IL-1β and IL-18 leads to a reduction in inflammation caused by viral infection. Furthermore, the administration of a LTB4 treatment in a fatal IAV infection model can mitigate the excessive NLRP3 inflammasome activation and reduce IAV-induced severe pulmonary damage. These findings illustrate the protective function of LTB4 in fatal IAV infection by mitigating the severe inflammation induced by the virus.